2004
DOI: 10.1128/jcm.42.12.5620-5623.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Mechanisms of Erythromycin Resistance in Group A and Group B Streptococcus : Implications for Reporting Susceptibility Results

Abstract: Increased rates of erythromycin resistance among group B Streptococcus (GBS) and group A Streptococcus (GAS) have been reported. Cross-resistance to clindamycin may be present, depending on the mechanism of resistance. We determined the prevalence of macrolide-resistant determinants in GBS and GAS isolates to guide the laboratory reporting of erythromycin and clindamycin susceptibility. Susceptibilities were determined by the disk diffusion and broth microdilution methods. Inducible and constitutive resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 20 publications
6
71
3
3
Order By: Relevance
“…In Belgium, as determined by the National Reference Centre for GBS, macrolide resistance increased from 10.4% in the early 2000s to 33% among invasive strains isolated from 2008 to 2011 [59]. These figures are consistent with similar reports from Europe [61][62][63][64][65], North America [60,[66][67][68][69][70], and Asia [71,72], except some surveillance studies in Sweden reported 510% [73], thus showing some geographical differences. Different mechanisms account for the acquired resistance to macrolides in streptococci [74].…”
Section: Gbs Clinically Relevant Antimicrobial Susceptibility Profilesupporting
confidence: 81%
“…In Belgium, as determined by the National Reference Centre for GBS, macrolide resistance increased from 10.4% in the early 2000s to 33% among invasive strains isolated from 2008 to 2011 [59]. These figures are consistent with similar reports from Europe [61][62][63][64][65], North America [60,[66][67][68][69][70], and Asia [71,72], except some surveillance studies in Sweden reported 510% [73], thus showing some geographical differences. Different mechanisms account for the acquired resistance to macrolides in streptococci [74].…”
Section: Gbs Clinically Relevant Antimicrobial Susceptibility Profilesupporting
confidence: 81%
“…This can be regarded as a low rate of incidence compared to incidence data from Asia, Europe, the United States, and Canada (6,16,24,40,42); but similar results were also found in other Latin American and Nordic countries (18, 23, 35, 36, 37). This could be attributed to the more intense clinical use of these antibiotics in Asia, Europe, the United States, and Canada.…”
Section: Discussionsupporting
confidence: 56%
“…Erythromycin and clindamycin are recommended when risks of anaphylaxis or therapeutic failure are present. However, resistance to erythromycin and clindamycin has increased in many countries in North America (2,6,16,40), Europe (21,22,42,45), and Asia (24) but not in Brazil (18,50) and other Latin American countries (23,35,36). Such a resistance profile is mainly due to two mechanisms: a methylasemediated target site modification and an active efflux pump (53).…”
mentioning
confidence: 99%
“…In addition, many S. agalactiae isolates carrying ermTR have been shown to display an inducible macrolides, lincosamides, and streptogramin B resistance, which can only be detected by a double-disk diffusion test, possibly explaining why ermTR-positive isolates tested here were clindamycin sensitive by single-disk testing (15). Importantly, ermB-positive bovine isolates represented a different ribotype than ermB-positive human isolates, indicating a different clonal origin of human and bovine ermB-positive isolates, possibly through horizontal gene transfer either between S. agalactiae or another closely related organism, e.g., Streptococcus pyogenes, which was previously shown to carry ermB (16).…”
Section: Discussionmentioning
confidence: 86%